Alfentanil during rapid sequence induction with thiopental 4 mg/kg and rocuronium 0.6 mg/kg: tracheal intubation conditions. Issue 10 (14th July 2015) - Abou‐Arab, M. H.; Feiner, J. R.; Spigset, O.; Heier, T.
<x xml:space="preserve">Abstract</x> Background Opioids have become an integral part of anaesthesia induction. We aimed to determine the dose of alfentanil needed to obtain perfect tracheal intubation conditions during rapid sequence induction with standard doses of thiopental and rocuronium, where laryngoscopy was initiated 55 s after commencement of drug administration. The influence of covariates (sex, body weight, age, alfentanil plasma concentration at laryngoscopy) was tested. Methods Eighty‐four healthy individuals were randomly assigned to receive one of the seven assessor‐blinded alfentanil doses (0, 10, 20, 30, 40, 50 and 60 μg/kg) in conjunction with thiopental 4 mg/kg and rocuronium 0.6 mg/kg. For drug administration, 15 s was allowed. Laryngoscopy was initiated 40 s after rocuronium and tracheal intubation concluded within 70 s after commencement of drug administration. Alfentanil doses associated with 50%, 90% and 95% probability of perfect intubation conditions were determined with logistic regression. Multiple logistic regressions were used to test the influence of covariates. The relationship between alfentanil dose and concentration at laryngoscopy was analysed with linear regression. The effects of covariates on plasma concentrations of alfentanil were tested with multiple linear regressions. Results Perfect intubation conditions of 95% probability was obtained with 56 μg/kg (confidence intervals 44–68). None of the covariates were significant predictors of perfect intubation conditions. Alfentanil plasma concentration correlated with dose and increased with increasing body weight (1.7 ng/ml/kg). Conclusion Perfect intubation conditions during rapid sequence induction can be obtained with clinically relevant doses of alfentanil in most healthy patients anaesthetized with thiopental 4 mg/kg and rocuronium 0.6 mg/kg.